Cost and Time Optimization In Retaining Wall Construction Through The Application of Value Engineering on The Bendung-Bantengan Road Section, Mojokerto District - Fairuz Rahman, Refa; Oetomo, Wateno; Marleno, Risma (Green Publisher Indonesia, 2025)
Mojokerto is a region in East Java with strategic geographical and economic significance, serving as a key area for regional connectivity and growth. However, the Bendung-Bantengan road section has experienced considerable damage due to inadequate retaining walls, leading to road subsidence, cracks, and increased maintenance costs. These challenges necessitate effective soil stabilization measures to ensure the safety and functionality of the infrastructure. This study explores the application of Value Engineering (VE) to optimize the planning and construction of retaining walls in the region. Utilizing secondary data from topographic surveys and triaxial soil tests, this research evaluates three design alternatives to identify the most efficient solution. The analysis revealed that Alternative 1 demonstrated the highest cost efficiency, achieving a reduction in construction expenses by IDR 284,244,698.00 through the optimization of structural dimensions and material usage. In addition to cost savings, the implementation of VE also contributed to a shortened project timeline, reducing the completion period to 121 days from the originally planned 180 days. The design maintained its quality and structural stability, effectively resisting lateral soil pressure while mitigating erosion risks. This study underscores the significance of incorporating VE during the planning stages of infrastructure projects. By balancing cost efficiency, quality, and sustainability, VE enhances project value and ensures long-term resilience. The findings provide a strategic framework for future infrastructure projects, promoting sustainable and economically viable solutions for regions with challenging geotechnical conditions. VE’s integration into construction practices highlights its transformative potential in achieving efficient and durable infrastructure development.